Hubungan Pola Asuh dan Tingkat Pendidikan Orang Tua terhadap Perkembangan Emosional pada Anak Pra Sekolah di TK Paud Pakonda - Putri Korlianda Indri Manna; Feva Tridiyiwati (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT The emotionality of preschoolers can be high or low, which can be determined by several factors, including the parenting style applied and the educational background of the mother which influences the emotional state of the child. Purpose to determine the relationship between parenting and educational level of parents on emotional development in pre-school children. The type of research used is quantitative with a descriptive and analytic research design, with a cross-sectional approach that was carried out in Pakonda PAUD Kindergarten. The results of the chi square test showed that the significance value (Asymp. Sig 2 tailed) was 0.38 so that the significance value was less than 0.05 (P>0.05). Because the significance value is less than 0.05, there is a relationship between Parenting Style and Children's Emotional Development. the significance value (Asymp. Sig 2 tailed) is 0.045 so that the significance value is less than 0.05 (P<0.05). Because the significance value is less than 0.05, there is a relationship between the Education Level of Parents and Children's Emotional Development. There is a relationship between parenting style and parental education level on the emotional development of preschoolers in Paud Paud Kindergarten.  Keywords: Parenting Style, Mother's Level of Education, Emotional Preschool Children ABSTRAK Emosional anak prasekolah dapat tinggi atau rendah dapat ditentukan oleh beberapa faktor diantaranya pola asuh yang diterapkan dan latar belakang Pendidikan ibu yang mempengaruhi emosional anak. Tujuan untuk mengetahui Hubungan Pola Asuh Dan Tingkat Pendidikan Orang Tua Terhadap Perkembangan Emosional Pada Anak Pra Sekolah. Jenis penelitian yang digunakan ialah kuantitatif dengan desain penelitian deskripsi analitik, dengan pendekatan cross sectional yang dilakukan di TK paud Pakonda. Hasil uji chi square menunjukan bahwa nilai signifikasi (Asymp. Sig 2 tailed) sebesar 0.38 sehingga nilai signifikasi lebih kecil dari 0.05 (P>0.05). Karena nilai signifikasi lebih kecil dari 0.05 maka terdapat hubungan antara Pola Asuh Orang Tua dengan Perkembangan Emosional Anak. nilai signifikasi (Asymp. Sig 2 tailed) sebesar 0.045 sehingga nilai signifikasi lebih kecil dari 0.05 (P<0.05). Karena nilai signifikasi lebih kecil dari 0.05 maka Terdapat hubungan antara Tingkat Pendidikan Orang Tua dengan Perkembangan Emosional Anak. Terdapat hubungan antara pola asuh orang tua dan tingkat Pendidikan orang tua terhadap perkembangan emosional Anak Prasekolah di TK paud Pakonda. Kata Kunci: Pola Asuh, Tingkat Pendidikan Ibu, Emosional Anak Prasekolah